Correlation and path coefficient analyses of cowpea (Vigna unguiculata L.) landraces in Ethiopia - Walle, T.; Mekbib, Firew; Amsalu, B.; Gedil, Melaku A (Scientific Research Publishing, Inc., 2018)
Understanding the nature and extent of association between yield and yield related traits is the prerequisite study for any underutilized crop improvements of sustainable genetic enhancement. However, there is a lack of sufficient information on seed yield and related trait correlation and path coefficient analysis of cowpea in Ethiopia. To fill the existing knowledge gap, the present study was conducted to determine the nature and extent of phenotypic and genotypic correlation and path coefficient analysis among 18 quantitative traits. A total of 324 cowpea landraces were tested in 18 × 18 simple lattice design at Melkassa Agricultural Research Center and Miesso sub center during 2016 cropping season. The magnitude of genotypic correlations was higher than phenotypic correlations in most traits at both locations; this implies that the traits under consideration were genetically controlled. Seed yield was positively and highly significantly correlated with most of the traits at phenotypic and genotypic levels, indicating the presence of strong inherited association between seed yield and the other 17 traits. Almost all traits genotypic direct and indirect effects were higher than the phenotypic direct and indirect effects; this indicated that the other traits had a strong genetically inherited relationship with seed yield. Genotypic path coefficient analysis revealed that days to flowering, biomass and harvest index at Miesso, and seed thickness, plant height, days to maturity and biomass at Melkassa had relatively high positive direct effect on seed yield. However, seed width and hundred seed weight had exerted negative direct effect on seed yield at each location. Phenotypic path coefficient analysis showed that biomass and harvest index had exerted high positive direct effect on seed yield at both locations. From these results it can be concluded from this study that seed yield in cowpea can be improved by focusing on traits pod length, seed length, seed thickness, seed width, biomass and harvest index at both locations. The information obtained from this study can be used for genetic enhancement of cowpea thereby developing high yielding varieties.